Naive Bayesian Classifiers for Purposes of Medical Differential Diagnostics - Kondrashova, N.; Pavlov, V. (Індуктивне моделювання складних систем, 2014)
A distinctive feature of this work is grouping naive Bayesian classifiers in the scheme of "one against all" and using the extended features space. Metric and categorial variables are present in the original sample. The scheme of "one vs. all" with the use of other methods of classification gives an improvement in the accuracy of the differential diagnosis on exam sample compared to a single Bayesian classifier, but not in the case of the Naive Bayesian classifiers. The obtained results allow us to compare methods accuracies with such as GMDH and canonical discriminant analysis in solution of classification problem. Відмінною особливістю даної роботи є ансамблювання наївних Байєсівських класифікаторів в схемі «один проти всіх» і використанні розширеного простору ознак. У первинній вибірці присутні метричні і категорійні змінні. Схема «один проти всіх» із застосуванням інших методів класифікації дає поліпшення на екзамені точності диференціальної діагностики порівняно з єдиним класифікатором, але не у випадку наївних Байєсівських класифікаторів. Отримані результати точності дозволяють порівняти їх з результатами інших методів розв'язання задачі класифікації: таких як МГУА і канонічний дискримінантний аналіз. Отличительной особенностью данной работы является ансамблирование наивных Байесовских классификаторов в схеме «один против всех» и использовании расширенного пространства признаков. В исходной выборке присутствуют метрические и категориальные переменные. Схема «один против всех» с применением других методов классификации дает улучшение на экзамене точности дифференциальной диагностики по сравнению с единым классификатором, но не в случае наивных Байесовских классификаторов. Полученные результаты точности позволяют сравнить их с результатами других методов решения задачи классификации: таких как МГУА и канонический дискриминантный анализ.